Haematological Profile of Preterm Neonates:An Experience of A Specialized Tertiary Hospital in Dhaka, Bangladesh - Jahan, Asmay; Nahar, Nazmun; Akhter, Afroza; Sarker, Mukta; Rahman, Fahmida (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: A complete blood count(CBC) elements that are abnormally high or low can influence our clinical decisions. However, the reference ranges for the various CBC elements in neonates change considerably in respect to gestational age. Objective: To observe and correlate gestational agerelated changes in the haematological profileof the preterm neonates. Methods: This cross-sectional, prospective study was conducted between July 2007 and January 2008 in collaboration between Department of Paediatrics and Department of Obstetrics & Gynaecology of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) Hospital, Dhaka, Bangladesh. A total of 49 preterm newborns of different gestational age (28 males and 21 females) included in this study.They were divided into three groups based on their gestational age: group I (30 weeks; n=11), group II (31-33 weeks; n=17) and group III (34-36 weeks; n=21). Within 48 hours of delivery, 1 ml venous blood was collected from each neonate and was sent to the Department of Clinical Pathology of the same hospital. Complete blood count (CBC) was done by using Abbott’s Cell-Dyn 3200 Automated Hematology Analyzer. Results: Significant differences were observed in total count of RBC, WBC, and platelet among those three groups. However, differential count of WBC, heamoglobin level, and haematocrit value among those three groups showed no significant differences (P>0.05). Gestational age showed a positive correlation with total count of RBC (r=0.216; P<0.05). Gestational age had also a positive correlation with neutrophil (r=0.448; P<0.001). Besides, gestational age was negatively correlated with lymphocyte (r=-0.389; P<0.001) However, gestational age did not bear any correlation with total count of WBC, monocyte, and eosinophil. Finally, gestational age was found to bear a positive correlation with heamoglobin level (r=0.412; P<0.001) and haematocrit value (r=0.382; P<0.001). Conclusion: Our data suggest that differences exist in different haematological parameters among preterm neonates of different gestational age. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 275-279